Sedative Hypnotic Effectiveness Activity of Lagenaria siceraria Extract on Swiss Webster White Male Mice - Niza, Hairun; Putri, Nadilah; Marpaung, Mauritz Pandopo; Afriliza, Dini; Wilsya, Mayaranti (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2024)
Introduction: The rising prevalence of sleep disorders and concerns about conventional sedative medications' side effects has created an urgent need for safer therapeutic alternatives. Aims: This study investigated the sedative-hypnotic properties of Lagenaria siceraria fruit ethanol extract in a controlled laboratory setting using Swiss Webster male mice. Methods: The research employed a randomized design with 28 male mice (2-3 months old, 20-30 grams) divided into seven groups. Two control groups received either 0.5% NaCMC (negative control) or 0.013 mg/kgBW Diazepam (positive control). The remaining five experimental groups were administered L. siceraria extract at doses ranging from 21 to 49 mg/kgBW. All treatments were administered orally under controlled conditions. Statistical analysis using two-way ANOVA revealed significant differences between treatment groups (p<0.005). Result: Subsequent Duncan's test analysis demonstrated that the highest dose of L. siceraria extract (49 mg/kgBW) produced sedative-hypnotic effects comparable to the standard Diazepam treatment. This finding suggests that L. siceraria extract could potentially serve as a natural alternative to conventional sedative medications. Conclusion: The results of this study provide compelling evidence for the sedative-hypnotic properties of L. siceraria extract, warranting further investigation into its mechanism of action and potential therapeutic applications. Future research should focus on establishing optimal dosing regimens and evaluating long-term safety profiles before clinical implementation can be considered.